Racial stratification, sex and mental ability: A comparison of five groups in Trinidad - Shangi, Lennard M.
A study of mental ability and reading comprehension as a function of sex and race in Trinidad contradicts a large body of North American literature advocating a hereditary-related Black intellectual inferiority. Results suggest that intellectual differences between racial groups in a given society reflect variables associated with racial stratification
Keywords: Cognitive ability